PWE-068 Prevalence and outcomes of pancreatic cystic lesions in liver transplant recipients: a pilot study from a liver transplant centre. (June 2019) - (Geri) Keane, Margaret; Reffitt, David; Harrison, Philip; Devlin, John; Joshi, Deepak
Abstract : Introduction: Incidental small pancreatic cystic lesions (PCLs) are common present in 1–2% of the population undergoing CT for non-pancreatic indications. They are increasingly being identified on preoperative imaging of patients undergoing orthotopic liver transplantation (OLT). Most PCL are benign but a proportion, namely intraductal papillary mucinous neoplasms (IPMNs) and mucinous cystic neoplasms (MCNs) harbour malignant potential. There is growing evidence that liver transplant recipients are at increased risk of extrahepatic malignancy. Whether the natural history of PCL in liver transplant recipients is the same as the general population in uncertain. The aim of this study was to look at the incidence and progression of PCL in liver transplant recipients. Methods: A pilot series of patients from a large UK liver transplant centre, were included. Between January 1990 and December 2017, a proportion of cases were selected from our consecutive database of liver transplant patients. Results: 238 patients were included. PCL were present in 4% (9/238), 8/9 were male. End stage liver disease was due to alcohol related liver disease in 5 cases, Primary Sclerosing Cholangitis in 3 and was unknown in 1. Follow-up was undertaken by MRI annually. During the median follow up of 79 months (range 33–288 months) all PCL in the liver transplant patients on long-term immunosuppression remained stable in size. One developed mild dilation of the main pancreatic duct but no other features of concern were observed. Conclusion: The prevalence of PCLs in liver transplant recipients was similar to that of the general population. PCL do not appear to have an accelerated malignant potential in post liver transplant patients, indicating the current International and European surveillance guidelines are likely to be applicable in this group.